NILAI-NILAI PENDIDIKAN ISLAM DALAM BUDAYA BATUYANG MAULID MASYARAKAT SUKU BAKUMPAI DI KELURAHAN JAMBU KABUPATEN BARITO UTARA - Jarina Jarina; Normuslim Normuslim; Asmawati Asmawati (Jurnal Bilqolam Pendidikan Islam, 2025)
One of the cultures of the Bakumpai tribe is Batuyang Maulid, which is a procession of maayun anak which is carried out together in the Mosque in the month of Rabiul Awal during the celebration of the Prophet's Birthday. In the implementation of Batuyang Maulid there are various rituals and Islamic educational values ​​in it. However, along with the development of the era and the entry of various external influences, there are concerns that the Batuyang Maulid culture will fade. This can have an impact on reducing the understanding of the younger generation towards Islamic teachings contained in the Batuyang Maulid culture. Therefore, the purpose of this study is to find out the implementation of the Batuyang Maulid culture of the Bakumpai tribe in Jambu Village and the Islamic educational values ​​contained in the Batuyang Maulid culture of the Bakumpai tribe in Jambu Village. To achieve this goal, this study uses a qualitative method. Then, the validity of the data is tested through triangulation. The results of the study show that the implementation of the Batuyang Maulid culture begins with an opening after which the reading of tawasul and chanting the sholawat syaraful anam or the Maulid barzanji poem while the child is swung back and forth. Every time the asyrakal article is finished chanting, a mixture of potpourri and silver coins are scattered in the air. After the swinging procession has been completed, the next step is to sprinkle fresh water on the child with the aim of not crying the last prayer. The values ​​of Islamic education in the Batuyang Maulid culture include the value of aqidah education, the value of worship education and the value of moral education.